Towards designing better contracts: Assessing contract preferences of small farmers and buyers: Evidence from a choice experiment in cotton and tea schemes in Malawi: Synopsis - Ochieng, Dennis O. (International Food Policy Research Institute, 2020)
While contract farming provides opportunities to link smallholder farmers to markets, its sustainability depends on how the interests of both farmers and buyers are addressed. Previous studies analyze farmers’ preferences for contracts, but buyers’ preferences for contracts and design attributes are hardly examined. The author contributes to the knowledge gap by analyzing farmers’ and buyers’ preferences for contracts and design attributes, and the similarities and differences in preferences using a discrete choice experiment with 505 cotton farmers and 512 tea farmers in southern Malawi.